Library Service Strategies in Increasing Student Reading Interest: Strategi Pelayanan Perpustakaan dalam Meningkatkan Minat Baca Siswa - Athiyallah, Arina; Qazi Zada, Mohd Ziaolhaq; Utarini, Viola Sakinah; Alifah, Rifda (STAI Publisistik Thawalib Jakarta, 2024)
Reading is important for students as it will influence their skills and knowledge. The research aims to explain and describe library service strategies in enhancing students' reading interest at Budi Cendekia Islamic School Junior High School and Al-Hasra Senior High School. The research method employed a qualitative case study approach. Data collection techniques included documentation, observation, and interviews. Data processing involved reduction, data presentation, and drawing conclusions. Data validity was ensured through credibility and confirmability. Research findings: (1) Reading interest analysis: students have a high interest in reading during breaks, free periods, and books that meet their needs. (2) Service strategies: provision of fiction books, selection of reading ambassadors, procurement of relevant learning materials, book provision surveys, creating reading corners, library electronic services, and literacy competitions. (3) Impact: increasing students' enthusiasm for reading inside or outside the library. Conclusion: library services have been operating at their maximum capacity to enhance students' enthusiasm for reading.